A Study of Corporate Social Responsibility as a Strategic Instrument to Create Competitive Advantage Through Adaptation to Change Business Environments: An Analysis with Structural Equation Modelling - Ratnawat; Rokhman, M. Taufiq Noor (International Journal of Psychosocial Rehabilitation, 2020)
Small and Medium Enterprises (SMEs) are important part of a country’s economy and one of the ideas of empowering SMEs in Indonesia is done through batik business. The trend to increase batik SMEs in order to create competition among batik SMEs in the area of East Java Province also faces competition with batik SMEs outside East Java province. The existence of CSR does not only apply to companies that have a large number of operational activities, but it has been carried out by a number of small and medium-sized businesses such as batik SMEs. This study seeks to explore the relationship of Corporate Social Responsibility with competitive advantage through adaptation to change the business environment by using structural equation modeling analysis. CSR programs conducted by SMEs give much contribution to achieve competitive advantage if those SMEs are able to adapt with the business environments changes.